PEMANFAATAN CITRA MULTISPEKTRAL UNTUK ANALISIS SIHU PERMUKAAN KOTA SURAKARTA TAHUN 2020-2024 - Arlindita, Yazinka Puri; Hidayati, Iswari Nur (UNM Geographic Journal, 2025)
Transformation of suburban areas into urban areas often results in the phenomenon of urbanisation which indirectly causes an increase in the dynamics of land use land cover (LULC) changes and changes in the distribution and intensity of Land Surface Temperature (LST). In this study, we examined the relationship of LULC dynamics to the spatial pattern of LST in Surakarta City through Landsat 8 OLI and TIRS image data in 2020 and 2024. Determination of LULC dynamics is done through supervised classification method, and single channel algorithm method to regress thermal data into spatial distribution of Surakarta City LST. The results of LULC and LST processing were spatially regressed using Geographically Weighted Regression (GWR) features to see the correlation and statistical calculations to see the level of surface temperature in each land use class. The results showed a positive change in built-up area which includes residential and non-residential buildings of 6.59 hectares in 2024, while vegetation land experienced a negative change of 487.72 hectares. LST processing results show changes in maximum and minimum temperatures, with a range of 23-30.1oC in 2020 to 24.85-30.5oC in 2024. Spatially, the maximum surface temperature distribution is on residential built-up land, while the lowest surface temperature is on vegetation land, especially non-agricultural vegetation. The results of this study can help the government in creating a spatial layout of Surakarta City that pays attention to the environment through the development of green spaces in several high-class locations.